Certification and Professional Preparation of School Social Workers, School Psychologists, and School Counselors. Issue 3 (13th July 2021) - Mitchell, Brandon; Frey, Andy; Kelly, Michael S
Abstract: Educational leaders are faced with the difficult task of providing optimal services to all students. Among their many challenges is to choose between a variety of professionals whose mission is to improve outcomes by addressing largely nonacademic risk factors that affect students' ability to benefit from their educational experiences. Specialized instructional support personnel are often hired to help remove barriers to learning and improve student outcomes; however, certification requirements for these professionals vary by discipline and state. The purpose of this article is to replicate Altshuler and Webb's analysis of certification requirements for school social workers, school psychologists, and school counselors. To do so, the authors adopted a comparative case study approach to collect, identify, compare, and contrast extant documents related to state certification, including degree, education-specific coursework, practicum/internship experiences, and examination requirements. Results indicate that although school social work certification has become more rigorous, its requirements remain more varied across all categories reviewed compared with those for school psychologists and school counselors. The article concludes with recommendations for practice, policy, and research.